Clays enhanced with niobium: potential in wastewater treatment and reuse as pigment with antibacterial activity - Jaerger, Silvia; Appelt, Patricia; da Cunha, Mario Antônio Alves; Ayma, Fabián Ccahuana; Schneider, Ricardo; Bittencourt, Carla; Anaissi, Fauze Jacó (Beilstein Journal of Nanotechnology, 2025)
Bentonite clay sourced from the Guarapuava region, Brazil, was modified with niobium oxide (BEOx) and niobium phosphate (BEPh) to act as an adsorbent and photocatalyst in the remediation of wastewater containing methylene blue (MB) dye. Additionally, colored materials were evaluated for their potential as antibacterial hybrid pigments. The bentonite clay modified with niobium was prepared by a solution containing swelling clay mixed with niobium oxide (NbOx) and niobium phosphate (NbPh) in a water solution; after that, the suspension was calcinated. X-ray diffractometry, X-ray photoelectron spectroscopy, and laser-induced breakdown spectroscopy assessed the modifications induced by the incorporation of niobium compounds into the clay, confirming the presence of niobium in the bentonite clay. Following characterization, the BEOx and BEPh samples were used as adsorbents or photocatalysts for treating solutions containing the MB dye (400 mg·L−1) at 25 °C. The results showed adsorption and photocatalysis efficiency above 94% for both samples. The blue-colored BEOx and BEPh samples were then applied as a hybrid pigment. The power pigment and its dispersion in colorless paint were evaluated by the CIEL*a*b* color space, and the ΔE parameters show values above 12, indicating a very strong color parameter difference. Subsequently, the efficacy of BEOx and BEPh as a hybrid pigment was assessed using the minimum inhibitory concentration (MIC) assay against two bacteria strains: Bacillus cereus (ATCC 10876) and Proteus mirabilis (ATCC 35649). The analysis revealed remarkable antibacterial activity against Proteus mirabilis, suggesting a preferential selectivity for Gram-negative bacteria.
Keywords: adsorption; bentonite; hybrid pigment; niobium; photocatalysis; water remediation